Complex surgery and optimal consent: A variety of opinions exist among healthcare professionals. Issue 6 (December 2022) - Clancy, Cillian; McCawley, Niamh; Burke, John P.; McNamara, Deborah
Abstract: Background: Establishing healthcare professional's views on optimal consent in complex surgery could guide tailored consent policy, improving the process in challenging scenarios. To date, no studies have established if professionals of differing specialities agree on major aspects of consent in areas such as emergency surgery and cancer surgery. Methods: An anonymous web based survey was distributed to a variety of disciplines in a tertiary referral centre. Questions regarding optimal methods and timing of consent in emergency and cancer surgery were posed. Comparative analyses of quantitative data were performed using chi-squared test. Results: 57 responses were received from doctors and nurses of varying disciplines. Differences were found between doctors of separate specialities and nurses in opinion of optimal timing of consent (p = 0.02), consent validity over time (p < 0.001) and the utility of introducing more specific consent policy (p = 0.01). Almost all respondents agreed that healthcare professionals have differing ideas of what consent is. Conclusions: This study demonstrates differences in opinion regarding optimal consent for cancer and emergency surgery. Consideration should be given to developing consensus among healthcare professionals regarding what consent for complex surgery constitutes.